Videoaulas na formação inicial de professores de matemática - Prado, Paulo Victor Machado (2023)
This research aims to discuss the use of video lessons in the initial Mathematics teachers’ training process. The motivation for this study was the pandemic situation, which caused several changes in learning methods, resulting in different ways of trying to make students’ learning possible. Video lessons popularity has risen and have become one of the most used tools. The research uses a qualitative approach by adopting ways in which the researcher aimed to interpret the research object through a point of view that moves away from empirical studies, considering the history and culture of its members. Four undergraduate students attending to the OPP (Practical Pedagogical Workshop) remotely, as part of a Mathematics teacher training course at a public university, participated in the project. Their instruments were data acquiring, field notes, questionnaires, semi-structured interviews, and remote classes recordings, besides the material produced and made available in the subject Virtual Learning Environment (AVA) by the students who were enrolled during the semester the investigation occurred. After collecting information, it focused on understanding how video lessons and further activities were elaborated and how they contributed with Mathematics teachers’ training and educational process. Using the TPACK model, it developed two main analysis objectives to know: understanding the formative trajectory through video lessons in the Degree in Mathematics course subject and analyze the authorship projects process of the undergraduation in Mathematics students related to the educational work using math video lessons. As a result of the educational work realized along with the creation and production of video lessons in the Mathematics teachers’ initial training, in this research’s final considerations, it concluded that: 1) using video lessons as a work tool can be valuable to the math teachers’ training, allowing them to improve their teaching skills and develop new pedagogical strategies to make their students learning more efficient and interesting, 2) all this video lessons work is not easy; actually, it goes far beyond from being just a simple video recording, 3)the importance of using the TPACK model in the digital didactic material production, which presented itself as an efficient strategy to enhance the learning quality, and consequently the students’ education, and 4) the importance of TPACK in the elaboration of more effective and engaging classes. As a result of this research, a digital product was developed as an ebook titled: "Digital Graphic Materials Production Manual for Mathematics Teacher Formation.